Strategi Pengembangan Keilmuan dan Kualitas Pendidikan dalam Mencapai Indikator Kinerja Umum (Perspektif Administrasi Dan Kebijakan Publik) - Marlon Sihombing (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
Knowledge dynamics, likened to perishable food by Samuel Arbesman (2012), underscore the need for continuous development and maintenance to prevent obsolescence. Thomas Jones (1966) reported that half of an engineer's knowledge becomes outdated within 10 years. By 2019, this obsolescence period was estimated to be only 2.5 to 5 years (Agus Pranusinto, 2020). Therefore, knowledge maintenance and development must be done dynamically, driven by scientific validity and policy relevance. In public administration, scientific validity involves generalizability, universality, and replicability, while policy relevance ensures contextual solutions to complex social issues (Moeljarto Tjokrowinoto, 2013). Synergy between vision and precision is key; vision strengthens conceptual validity, while precision enhances methodology. Factors such as social dynamics, global competition, technological revolutions (Industry 4.0 and 5.0), and the COVID-19 pandemic necessitate adaptive knowledge development. Although technology offers opportunities, Indonesia's lag in various global indices underscores the importance of effective collaboration among all stakeholders. The pandemic demonstrates technology's potential for public service efficiency. Leveraging this success for academic development and educational improvement poses a significant challenge for policymakers and academics.